A comparative study on maximum power point tracking techniques for photovoltaic generation systems operating under fast changing environments. (September 2015) - Chen, Po-Cheng; Chen, Po-Yen; Liu, Yi-Hua; Chen, Jing-Hsiao; Luo, Yi-Feng
Highlights: Variable step-size MPPT methods are compared under various operating conditions. Various performance indices for comparing MPPT performance are proposed. Dynamic MPPT efficiency of variable step-size MPPT methods are also provided. Abstract: Perturb and observe (P&O) maximum power point tracking (MPPT) algorithms are commonly used in photovoltaic (PV) generation system (PGS) due to its ease of implementation. However, conventional fixed step-size P&O exhibits a trade-off between tracking speed and tracking accuracy. By contrast, variable step-size MPPT can achieve satisfactory tracking accuracy and speed while maintains advantage of simple calculation. This paper aimed to study the performance of different variable step-size P&O MPPT techniques. Initially, a MATLAB based PGS model is developed and validated. Then, variable step-size MPPT methods are compared in terms of energy captured, rise time, settling time and steady-state tracking accuracy under various operating conditions. Performance indices are also proposed in this paper to improve the reliability of the comparison. Finally, the response of these MPPT techniques is evaluated in rapidly changing weather conditions using international standard EN50530 to study the dynamic MPPT efficiency of each method. The pros and cons of each method are then summarized and relevant design suggestions are proposed.